Toward energy efficient microcontrollers and Internet-of-Things systems. (October 2019) - Al-Kofahi, Majd M.; Al-Shorman, Mohammad Y.; Al-Kofahi, Osameh M.
Abstract: In this paper, energy consumption of five common microcontroller (MCU) boards running a set of common functions and operations is studied. This includes a study of changing clock-speed, serial bit-rate, analog-to-digital conversion sampling rate, and compiler optimizations effects on the energy consumption. Additionally, the effect of using the on-chip floating point units (FPU) on the energy consumption is investigated. Results obtained in this study show that subtraction consumes slightly more energy than addition on all boards. Division consumes significantly more energy than any other operation. MCUs equipped with an FPU unit consume significantly less energy when performing an operation using the appropriate hardware unit. 8-bit, 16-bit, or 32-bit operations on a 32-bit MCU consume about the same amount of energy. The detailed results reported in this work serve as a valuable guideline for designers and developers to help build more energy-efficient embedded systems.